The long and winding road of Belarus to sovereignty and recognition - Kravchenko, Oleg I. (Journal of the Belarusian State University. International Relations, 2020)
The path of Belarus to its sovereignty and international recognition has been long, difficult and trying. Elements of international subjectivity originating from limited sovereignty have been present at different historical periods before Belarus’ gaining full-fledged independence in 1991. The authour studies external perception and legal view of the limited status of Belarus as a subject of international relations during the Soviet period through analysing a failed legislative effort in the US Congress to recognise and establish diplomatic relations with Byelorussian Soviet Socialist Republic.